STRATEGI PENINGKATAN KOMPETENSI PROFESIONAL GURU - Khudori, Saed Al; Ginting, Rahmadani Ftri (Sindoro: Cendikia Pendidikan, 2024)
Abstract This research is a qualitative study conducted through a literature review, focusing on various references related to strategies for enhancing teachers' professional competence. The teaching profession requires various professional qualifications. The quality of education largely depends on the quality of teachers. Only qualified teachers can perform their duties effectively. The primary responsibility of teachers is to educate the nation comprehensively, develop the personalities of Indonesian individuals, and cultivate scientists and skilled professionals. A qualified teacher is one who meets the personal criteria and possesses technical skills in teaching. This paper will discuss various strategies needed to improve teachers' professional competence." Penelitian ini merupakan studi kualitatif yang dilakukan melalui kajian pustaka, dengan fokus pada berbagai referensi yang berkaitan dengan strategi untuk meningkatkan kompetensi profesional guru. Pekerjaan guru memerlukan berbagai syarat profesional. Kualitas pendidikan sangat bergantung pada kualitas guru. Hanya guru yang berkualitas yang dapat melaksanakan tugasnya dengan baik. Tanggung jawab utama guru adalah untuk mencerdaskan bangsa secara menyeluruh, mengembangkan kepribadian masyarakat Indonesia, serta membentuk ilmuwan dan tenaga ahli. Guru yang berkualitas adalah mereka yang memenuhi syarat kepribadian dan memiliki kemampuan teknis dalam bidang keguruan. Tulisan ini akan membahas berbagai strategi yang diperlukan untuk meningkatkan kompetensi profesional guru.